2010
DOI: 10.1097/01.pra.0000367775.88388.96
|View full text |Cite
|
Sign up to set email alerts
|

Hatha Yoga for Depression: Critical Review of the Evidence for Efficacy, Plausible Mechanisms of Action, and Directions for Future Research

Abstract: A literature search for clinical trials examining yoga for depression uncovered eight trials: 5 including individuals with clinical depression, and 3 for individuals with elevated depression symptoms. Although results from these trials are encouraging, they should be viewed as very preliminary because the trials, as a group, suffered from substantial methodological limitations. We would argue, however, that there are several reasons to consider constructing careful research on yoga for depression. First, curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
225
3
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(240 citation statements)
references
References 69 publications
6
225
3
2
Order By: Relevance
“…[28][29][30][32][33][34][37][38][39][40][41][58][59][60] However, in a meta-analysis, Goyal et al (2014) found that meditation programs were similar in effectiveness to exercise, progressive muscle relaxation, or cognitive-behavioral therapy when compared with inactive controls. 31 In a meta-analysis of mindfulness-based therapies, Khoury et al (2013) found that these treatments were more effective than psychoeducation, supportive therapy, relaxation, and imagery, but they were not more effective than antidepressants or cognitivebehavioral therapy.…”
Section: Discussion and Suggestions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30][32][33][34][37][38][39][40][41][58][59][60] However, in a meta-analysis, Goyal et al (2014) found that meditation programs were similar in effectiveness to exercise, progressive muscle relaxation, or cognitive-behavioral therapy when compared with inactive controls. 31 In a meta-analysis of mindfulness-based therapies, Khoury et al (2013) found that these treatments were more effective than psychoeducation, supportive therapy, relaxation, and imagery, but they were not more effective than antidepressants or cognitivebehavioral therapy.…”
Section: Discussion and Suggestions For Future Researchmentioning
confidence: 99%
“…[28][29][30][31] Reviews of yoga as treatment for depression have found that participation in yoga-based interventions is associated with decreases in symptoms of depression and anxiety, improved quality of life and well-being, decrease in stress-related hormones (adrenocorticotropic hormone, cortisol), and improved sleep quality. [32][33][34] A study examining yoga as a complementary treatment for depressed patients taking antidepressants with residual depressive symptoms found that individuals who participated in a yoga intervention experienced significant reductions in depression, anxiety, anger, neurotic symptoms, limitations of role activities due to emotional problems, and low-frequency heart rate variability. 35 Mindfulness meditation involves intentionally paying sustained attention to ongoing sensory, cognitive, and emotional experience without elaborating or judging any part of that experience.…”
mentioning
confidence: 99%
“…First, it is a commonly practiced PA modality in the United States and is generally easily available through in-person classes or internetbased resources [52][53][54]. Second, my team's research suggests that pregnant women are explicitly expressed interest in yoga for symptom management [55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…Even in a gentle form as with yoga, PA appears to have important antidepressant and anxiolytic effects [44,[63][64][65][66]. Findings from numerous studies suggest that yoga-based interventions may help decrease psychological and physical symptoms of depression in a variety of populations [52,67,68]. Fifth, yoga can contribute to positive experiences with PA, 55 which may, in turn, increase PA selfefficacy and enhance motivation for future PA behaviors [69].…”
Section: Introductionmentioning
confidence: 99%
“…Yoga has been identified as beneficial to psychological and physical well-being in a variety of healthy and non-healthy populations [4][5][6][7][8][9][10][11][12][13], including cancer [14][15][16][17][18][19][20][21][22][23][24]. Reported benefits of participating in yoga for cancer patients include reduction of treatment-induced side effects and relief of symptoms of the disease itself [14][15][16]: these are often measured on validated quantitative scales.…”
mentioning
confidence: 99%